The morphological diversity of Chrysanthemum resulted from gamma ray irradiation - EMI SUSILA; ARI SUSILOWATI; AHMAD YUNUS (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Susila E, Susilowati A, Yunus A. 2019. The morphological diversity of Chrysanthemum resulted from gamma ray irradiation. Biodiversitas 20: 463-467. Chrysanthemum is a popular ornamental plant. The high market demand makes breeders develop new cultivars to meet market preferences. One way to get superior varieties of Chrysanthemum is by using gamma ray mutation induction which will increase the morphological variations. The purpose of this study is to determine the Chrysanthemum’s morphological diversity resulted from gamma irradiation through morphological markers. This experimental research used a completely randomized design (CRD) with one factor, i.e. radiation doses: 0 Gy (control), 10 Gy, 15 Gy, and 20 Gy. The observations were carried out qualitatively and quantitatively. The data obtained were analyzed using the SPSS 15.0 and the NTSYS (Numerical Taxonomy and Multivariate Analysis System) 2.02 program. The results showed that increasing the dose of gamma irradiation inhibited plant growth. Irradiation at 10 Gy and 20 Gy produced the most color changes in flowers compared to other doses. The basic color of 0 Gy irradiation is purple. Irradiation at 10 Gy and 20 Gy produced dark purple and deep red. Quantitative data showed that the treatment of gamma ray irradiation significantly affected the leaf length, leaf width, stem diameter, stem length, and diameter of flowers. The irradiation also caused changes in shape and texture of the leaves. The dendrogram showed that 20 Gy irradiation resulted the most diverse morphology compared to the control, 10 Gy and 15 Gy.